SLCO1B1 *15 allele is associated with methotrexate‐induced nausea in pediatric patients with inflammatory bowel disease - Rishi S. Mehta; Zachary L. Taylor; Lisa J. Martin; Michael J. Rosen; Laura B. Ramsey (Wiley, 2022)
Abstract Low‐dose methotrexate (MTX) is an immunosuppressant used to treat inflammatory bowel disease (IBD). SLCO1B1 genetic variation has been associated with delayed MTX clearance and increased toxicity. The purpose of this study was to evaluate the association between SLCO1B1 genetic variation and MTX‐induced nausea in children with IBD. We performed a single center retrospective chart analysis of 278 patients who were prescribed MTX for IBD. Two hundred two patients had banked DNA and were genotyped for three SLCO1B1 single nucleotide polymorphisms (SNPs; rs4149056, rs2306283, and rs11045819). Diplotypes were determined by combining the SNPs into *1, *4, *5, *14, *15, and *37 alleles. Incidence of nausea was abstracted from clinician notes. Prescriptions and demographics were extracted from the medical record. The cohort was 69.8% boys, 89.1% White, and 87.6% had a diagnosis of Crohn's disease with a mean age of 16.0 (± 3.8) years. MTX‐induced nausea was noted in 34% of the cohort. MTX‐induced nausea was associated with the number of reduced‐function *15 alleles (p = 0.034) and occurred 2.26 times more often in patients with at least one *15 allele who did not initiate MTX treatment with concomitant ondansetron (p = 0.034). MTX‐induced nausea was significantly independently associated with SLCO1B1 diplotype (p = 0.006) after controlling for MTX dose group and concomitant ondansetron. Our data demonstrate that the SLCO1B1 *15 allele is associated with MTX‐induced nausea in pediatric patients with IBD. Additionally, *15 allele carriers could benefit from a dose reduction of MTX to reduce exposure and treatment initiation with concomitant ondansetron to reduce nausea.